ANALYSIS OF PHYTOTOXICITY OF OIL-CONTAMINATED SOILS - Колєснікова, Л. А.; Федюшко, М. П. (Scientific Progress & Innovations, 2015)
The analysis of the toxic effects of crude oil on anatomical and morphological indices of leaf blade (LB) seedlings of spring wheat which were grown on soil with simulated contamination was held. There are three main effects of crude oil on the morphology of the LB model test culture were identified׃ stimulation of chlorine anabolic processes; resistance, the resistance of seedlings of spring wheat to the effects of oil contamination of soil; phytotoxic effect, causing the development of atrophy and destruction of chlorenchyma cells and leads to death of seedlings.